Texturized mung bean protein as a sustainable food source: effects of extrusion on its physical, textural and protein quality - Hossain Brishti, Fatema; Shyan, Yea Chay; Muhammad, Kharidah; Ismail-Fitry, Mohammad Rashedi; Zarei, Mohammad; Saari, Nazamid (Elsevier BV, 2021)
Despite being inexpensive and a sustainable source of plant protein, mung bean remains underutilized due to its hard-to-cook characteristics. The aim of this study is to produce texturized mung bean protein (TMBP) with desirable physical properties, through optimization of extrusion parameters determined as follows: 49.33% feed moisture, 80.66 rpm screw speed and 144.57 °C barrel temperature. Under these conditions, all physical properties (expansion ratio, bulk density, rehydration ratio, water absorption capacity and degree of texturization) are desirably altered. Microstructure analysis reveals fibrous structure that is aligned along the shear flow direction in TMBP while SDS-PAGE shows partial protein unfoldment that is crucial for protein fibril formation during texturization. Amino acid profile shows high retention of amino acids after texturization. Current study successfully demonstrates the optimized production of TMBP from mung bean protein with strong potential as meat extender to serve as a healthier option compared to animal proteins.Current work is conducted on a pilot-scale basis, from initial protein extraction up to final extrusion step. This allows food industry to readily adapt the processing parameters, as detailed in current work, for customized production of texturized mung bean protein.